Los procesos cognitivos básicos de atención y memoria y la comprensión lectora en estudiantes de primer ciclo de la carrera de Ingeniería Forestal de la Facultad Agropecuaria y de los Recursos Naturales Renovables de la Universidad Nacional de Loja, 2024. - León Soto, Jessenia Isabel (2024)
The general objective of the curricular integration project was to analyze the relationship between the basic cognitive processes of attention and memory with reading comprehension in first-year students of the Forestry Engineering program at the Faculty of Agriculture and Renewable Natural Resources of the National University of Loja, 2024. A mixed, descriptive, correlational, and cross-sectional approach was chosen, with a non- experimental design; the sample was non-probabilistic and consisted of 22 first-year students from the Forestry Engineering program. The instruments used were the d2 attention test, the RIAS subscale for memory, and the ICLAU for reading comprehension. Kendall's Tau-b was applied to assess the degree of relationship between the variables. The results showed that 86.4% of the participants had a low level of attention; 50% had a medium level of memory; and 77.27% achieved a medium level of reading comprehension. Finally, it was concluded that there is no significant correlation between the cognitive process of attention and reading comprehension, with a value of -0.01, which falls within a range of -0.01 to -0.19, indicating a very low negative correlation. Meanwhile, a Kendall’s Tau-b value of 0.15 was obtained for memory and reading comprehension, which falls within a range of +0.01 to +0.19, indicating a very low positive correlation.